2021
DOI: 10.1007/s10265-021-01314-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic events in the endosperm of amphiploid Avena magna × A. longiglumis

Abstract: This study analysed cytogenetic events occurring in the syncytial endosperm of the Avena magna H. C. Murphy & Terrell × Avena longiglumis Durieu amphiploid, which is a product of two wild species having different genomes. Selection through the elimination of chromosomes and their fragments, including those translocated, decreased the level of ploidy in the endosperm below the expected 3n, leading to the modal number close to 2n. During intergenomic translocations, fragments of the heterochromatin-rich C-ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…Intergenomic translocations have not been identified in A. agadiriana using our selected probes, and the FISH pattern suggested that this species may be of autopolyploid origin thus its affiliation to the AABB group and potential drivers shaping this species remain debatable. Both our karyotype analysis and the data obtained by different authors (Jellen et al, 1994;Luo et al, 2018a, b;Tomaszewska and Kosina, 2021;Yan et al, 2021;Peng et al, 2022) indicated that some intergenomic translocations could also influence the divergence of the CCDD Avena group. Some translocations between the C and D genomes in hexaploid oat species involved the same chromosomes as in tetraploid CCDD species (this paper; Badaeva et al, 2010;Yan et al, 2021) supporting the hypothesis that one of the species belonging to this oat group contributed to the evolution of hexaploid Avena species.…”
Section: Evolutionary Dynamics In Genus Avena In the Context Of Inter...supporting
confidence: 73%
See 3 more Smart Citations
“…Intergenomic translocations have not been identified in A. agadiriana using our selected probes, and the FISH pattern suggested that this species may be of autopolyploid origin thus its affiliation to the AABB group and potential drivers shaping this species remain debatable. Both our karyotype analysis and the data obtained by different authors (Jellen et al, 1994;Luo et al, 2018a, b;Tomaszewska and Kosina, 2021;Yan et al, 2021;Peng et al, 2022) indicated that some intergenomic translocations could also influence the divergence of the CCDD Avena group. Some translocations between the C and D genomes in hexaploid oat species involved the same chromosomes as in tetraploid CCDD species (this paper; Badaeva et al, 2010;Yan et al, 2021) supporting the hypothesis that one of the species belonging to this oat group contributed to the evolution of hexaploid Avena species.…”
Section: Evolutionary Dynamics In Genus Avena In the Context Of Inter...supporting
confidence: 73%
“…A certain advantage of the repetitive DNA probes over the whole genomic DNA probes used for in situ hybridization is observed (Tomaszewska et al, 2022). Despite the often perfect discrimination of genomes in allopolyploids/amphiploids using total genomic DNA isolated from a diploid species (Tomaszewska and Kosina, 2021), such probes are not applicable to distinguish closely related genomes such as those observed in Brassica (Alix et al, 2008), Triticum (Tang et al, 2018), Cenchrus and Urochloa tropical forage grasses (Rathore et al, 2022;Tomaszewska et al, 2022) or highly homologous A and D genomes in Avena (Linares et al, 1998). The parental species of amphiploids studied here are meiotically compatible in the crossing process, exhibiting sometimes partial sterility (Loskutov, 2001), and these data together with established genome composition of hybrids and amphiploids contribute to a better understanding of the complex evolutionary processes within the genus Avena.…”
Section: Identification Of Genomes In Artificial Hybrids and Amphiplo...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed no anomalous stamen formation in oat accessions. Therefore, the variability observed in the viability of pollen grains between the accessions of amphiploids and their parental species might be caused by disturbances in meiosis, resulting from the coexistence of several different genomes in the hybrid nuclei (Chen et al 1977;Tomaszewska and Kosina 2021). Meiotic anomalies can result in the formation of gametes with a reduced or increased number of chromosomes.…”
Section: Discussionmentioning
confidence: 99%